2004
DOI: 10.1038/nmat1238
|View full text |Cite
|
Sign up to set email alerts
|

Strong nonlinear current–voltage behaviour in perovskite-derivative calcium copper titanate

Abstract: The discovery of a giant dielectric constant of 10(5) in CaCu(3)Ti(4)O(12) has increased interest in this perovskite-type oxide. Here we demonstrate that, in addition to high permittivity, CaCu(3)Ti(4)O(12) has remarkably strong nonlinear current-voltage characteristics without the addition of any dopants. An intrinsic electrostatic barrier at the grain boundaries is responsible for the unusual nonlinear behaviour. The nonlinear coefficient of CaCu(3)Ti(4)O(12) reaches a value of 900, which is even greater tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
428
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 803 publications
(452 citation statements)
references
References 25 publications
19
428
5
Order By: Relevance
“…10,11 Rather, the dielectric response is due to barrier-layer capacitances associated with one or more of the following: grain boundaries, twin boundaries ͑or domain boundaries͒, dislocation networks, etc. [10][11][12] Specifically, the grain boundary barrierlayer capacitances are generally associated with non-Ohmic properties in metal oxide polycrystalline semiconductors. [13][14][15][16] Indeed, in addition to the remarkable and intriguing dielectric property, Chung et al 12 observed that potential barrier exists intrinsically in the grain boundary region, likely possessing a Schottky-type nature, according to Refs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 Rather, the dielectric response is due to barrier-layer capacitances associated with one or more of the following: grain boundaries, twin boundaries ͑or domain boundaries͒, dislocation networks, etc. [10][11][12] Specifically, the grain boundary barrierlayer capacitances are generally associated with non-Ohmic properties in metal oxide polycrystalline semiconductors. [13][14][15][16] Indeed, in addition to the remarkable and intriguing dielectric property, Chung et al 12 observed that potential barrier exists intrinsically in the grain boundary region, likely possessing a Schottky-type nature, according to Refs.…”
mentioning
confidence: 99%
“…Recently, we have also shown that such composites also present remarkable non-Ohmic properties 19 ͑i.e., a nonlinear coefficient value ␣ of ϳ65 in the traditional current density range of 1 -10 mA/ cm 2 and a͒ Author to whom correspondence should be addressed; electronic mail: prbueno@iq.unesp.br ϳ1500 in the current range of 3 -30 mA, the same range used by Chung et al 12 ͒.…”
mentioning
confidence: 99%
“…The non-linear behavior of the current observed in the CCTO film prepared on LNO indicates Schottky-type conductivity, typically observed in this material, with non-linear coefficient (a) of about 2. 29,30 Moreover, the symmetry of I vs. V curves in forward and reverse voltages was expected since that LNO phase displays a n-type 2012) conductivity which forms an ohmic contact with perovskite materials. 31,32 The Au top electrode has a work function value very close to the CCTO electron affinity which also forms an ohmic contact (as discussed below).…”
Section: B Rectifying Behaviormentioning
confidence: 97%
“…Similar relation between the quantity of domain boundaries and grain size is also reported in CCTO. 19,20 …”
Section: ͑4͒mentioning
confidence: 99%